Insight into border carbon adjustment: a visual bibliometric analysis from 2009 to 2024 - Xianting Bao; Yuran Jin (Humanities & Social Sciences Communications)
Abstract Over the past 15 years, research on Border Carbon Adjustment (BCA) advanced rapidly. However, comprehensive reviews of this field remained scarce, let alone visual analyses. Based on bibliometrics, this paper utilized CiteSpace and VOSviewer to analyze BCA-related literature from the WOSCC, CNKI, and arXiv databases spanning 2009 to 2024. The findings reveal three key insights: (1) Using WOSCC data, we construct the first knowledge network encompassing 46 countries, 464 institutions, 712 authors, and 122 journals. Through keyword timeline analysis, we trace the policy-driven thematic evolution of BCA research, while literature co-citation clustering identifies five global research hotspots: BCA mechanism design, policy efficacy assessment, socioeconomic impacts, supply chain complexities, and post-implementation governance strategies. (2) CNKI-based analysis highlights China’s transition from passive policy evaluation to proactive institutional innovation, offering a replicable framework for emerging economies. Meanwhile, arXiv publications emphasize technological innovations in emission reduction. (3) Emerging research frontiers coalesce around five directions: Multilateral rule games & North-South coordination, BCA policy refinement, Climate justice frameworks, AI/blockchain-driven carbon pricing and hybrid technology innovation, and advances in quantitative analytical tools. Furthermore, emerging economies are seeking context-specific solutions, such as China’s approach of integrating digital finance into the pathways toward achieving the dual-carbon goals.